A Chinese patent medicine’s long-term efficacy on non-dialysis patients with CKD stages 3–5: a retrospective cohort study - Chen, Hui-Fen; Lin, Yu-Jie; Han, Yan; Zhang, Xian-Long; Wang, Ruo-Bing; Chen, Jun-Hui; Pi, Ying; Fu, Li-Zhe; Tang, Fang; Jie, Xi-Na; Tang, Xiao-Na; Liu, Xu-Sheng; et al. (Frontiers in Pharmacology, 2024)
Background Chinese Patent Medicine is commonly used in China as important treatment to thwart the progression of CKD stages 3-5, among which Niaoduqing granules are a representative Chinese patent medicine, but its long-efficacy on CKD prognosis remains unclear. Methods Patients were grouped according to Niaoduqing granule prescription duration (non-NDQ group vs. NDQ group). SCr variation was compared using a generalized linear mixed model (GLMM). Multivariate Cox regression models adjusting confounding factors were constructed to explore the risk of composite outcomes (receiving RRT or eGFR<5 mL/min/1.73 m2, ≥50% decline in eGFR from baseline and doubling of SCr) in individuals with Niaoduqing granules. Results 1,271 patients were included with a median follow-up duration of 29.71 (12.10, 56.07) months. The mean SCr Z-scores for the non-NDQ group and NDQ group were -0.175 and 0.153, respectively at baseline (P=0.015). The coefficients of the NDQ group from Visit 1 to Visit 5 were -0.207 (95% CI: -0.346, -0.068, P=0.004), -0.214 (95% CI: -0.389, -0.039, P=0.017), -0.324 (95% CI: -0.538, -0.109, P=0.003), -0.502 (95% CI: -0.761, -0.243, P=0.000) and -0.252 (95% CI: -0.569, 0.065, P=0.119). The survival probability was significantly higher in the NDQ group (P=0.0039). Taking Niaoduqing granules was a significant protective factor for thwarting disease progression (Model 1: HR 0.654 (95% CI 0.489-0.875, P=0.004); Model 2: HR 0.646 (95% CI 0.476, 0.877, P=0.005); Model 3: HR 0.602 (95% CI 0.442, 0.820, P=0.001). Conclusion Long-term use of Niaoduqing granules improved SCr variation and lowered the risk of CKD progression by 39.8%.